(untitled) (International Conference on Education, Psychology and Humanities, 2026)
This article describes the content of an innovative methodological system that manages educational activities in organizing the process of developing independent thinking based on reading in primary school students. The study analyzed the mechanisms for the development of reflexive, interactive and independent cognitive activity of students on the basis of the exhibition” My Book“, the creation of a continuous Mutola environment through the integration of the classroom and Family Library, the methods” plot-adventure“,” Mutola notebook“,” thought “and the project” Mutola time". The results show that innovative approaches are effective in developing analytical, critical, and creative thinking in students.